The Effect of ESG Risk Rating and Leverage on Stock Returns with Profitability as a Moderating Variable in Mining Sector Companies Listed on the Stock Exchange Indonesia's Impact 2020-2024 - Christian Valentino Wahyu Leo; Siti Aisyah Hidayati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Stock returns in the mining sector on the Indonesia Stock Exchange (IDX) experienced high volatility during 2020-2024 due to commodity price fluctuations and the impact of the pandemic. This study aims to analyze the effect of ESG Risk Rating and leverage on stock returns, with profitability (ROE) as a moderating variable in mining companies listed on the IDX. Using quantitative explanatory research with panel data from 15 purposive sample companies (ANTAM, INCO, etc.), secondary data from financial reports, Sustainalytics ESG ratings, and daily stock prices were analyzed through EViews panel regression (Random Effects Model). The results show that ESG Risk Rating has a positive but insignificant effect (β=0.021966, p=0.0578), leverage (DER) has no significant effect (p=0.5248), and ROE fails to moderate both relationships (p>0.05). The model only explains 3.83% of the return variation (Adjusted R²=0.038). In conclusion, external factors dominate mining stock returns compared to internal financial metrics in the volatile Indonesian commodity market.